Edukasi Pasar Modal Berbasis Web pada Siswa SMA Negeri 17 Surabaya - Agustina Ratna Dwiati; Ellen Theresia Sihotang; Evi Sistiyarini; Zubaidah Nasution (Yayasan Literasi Sains Indonesia, 2026)
This Community Service Activity (CSA) was conducted for students of SMA Negeri 17 Surabaya to enhance their understanding of early investment in the capital market through a technical analysis approach. The activity was motivated by the lack of innovative economics learning materials and media related to capital market education, which has led to limited practical understanding among high school students. To address this issue, a more practical and contextual learning method was applied using training and simulation. The training introduced basic capital market concepts, while the simulation used the ChartNexus website to practice basic technical analysis. The CSA was implemented in three stages: planning, implementation, and evaluation. Planning involved coordination with the school to identify learning needs. The implementation was held for two and a half hours at Hayam Wuruk Perbanas University and attended by 10 students. Evaluation was conducted through direct observation and questionnaires. The results indicated improved participant understanding, with several students able to perform basic technical analysis. Participants also gave very positive feedback on the organization and delivery of the activity, indicating that the program was successfully implemented.